Crosstalk between Macrophages and Mesenchymal Stem Cells Regulated by Biomaterials and Its Role in Bone Regeneration. (17th September 2021) - Gong, Fan; Groth, Thomas; Tu, Chenlin; Zhao, Mingyan; Huang, Xinqia; Chu, Jiaqi
Abstract : Impaired bone healing caused by severe trauma, infection, and tumor resection is an extremely common phenomenon. Therefore, the treatment of bone defects represents a major clinical challenge worldwide. In such situations, the application of biomaterials is necessary for filling defects and promoting bone regeneration. Bone repair biomaterials having osteoconductive and osteoinductive properties can act as an appropriate template for the formation of new bone and induce the osteogenic differentiation of preosteocytes and stem cells. Thus, the influence of biomaterials on the regulation of osteogenesis of mesenchymal stem cells (MSCs) has been widely studied. However, immune response is also critical in bone healing; macrophages play pivotal and dynamic roles in bone regeneration. The interfacial properties of biomaterials that affect the adsorption of proteins and the adhesion function of cells require great attention in the field of bone tissue engineering because they are related to the crosstalk with the immune and bone or stem cells. Thus, selection of biomaterials or specific surface coatings may reduce local undesirable inflammatory responses and promote bone regeneration. This review provides a detailed overview of bone regeneration mechanisms and the interaction between immune cells and MSCs. Moreover, the influence of biomaterials on the regulation of functions of MSCs and macrophages and the macrophage-related inflammatory response triggered by biomaterials and its specific role in osteogenesis are discussed.